Faktor Risiko Penyakit Dekompresi Pada Nelayan Penyelam Di Pulau Barrang Lompo - Dian Rezki Wijaya; Ranti Ekasari; Lilis Widiatuty; Zil Fadhilah Arranury; Tri Addya Karini (Politeknik Kesehatan Makassar, 2021)
Decompression sickness is a disorder or disease caused by the release and increase of gas bubbles from the dissolved phase in blood or tissue due to the pressure drop that is often experienced by diving fishermen. Symptoms include dizziness, joint pain, paralysis, and even death. This study aimed to determine the risk factors of decompression disease in divers in Barrang Lompo Island. This study used a Case-Control Study design. The study population was all divers with 15-64 years of age, either suffering or not suffering decompression sickness. The research subjects were 47 cases and 94 controls obtained by accidental sampling. The results showed that the depth of diving (OR = 2.641; Cl 95% = 1.285-5.428), frequency of diving (OR = 4.067; Cl 95% = 1.939-8.531), and length of diving (OR = 3.872; Cl 95% = 1.657-9.052) were the risk factors of the decompression disease incidence on divers in Barrang Lompo Island. It is suggested to divers and all members who participate in the search to prepare a dive plan according to procedures related to depth, frequency, and duration of dives to reduce the incidence of decompression sickness.